A cross sectional study to assess perceived stress and stressors associated with it among undergraduate medical students in a private medical college of Uttar Pradesh, India - Chaudhary, Varsha; Upadhyay, Deepak; Singh, Shailendra Pratap; Singh, Arun; Joshi, Hari Shankar; Katyal, Rashmi (International Journal Of Community Medicine And Public Health, 2016)
Background: Stress is a state of an individual that results from the interaction of the individual with the environment which is perceived as threatening or threat to the well-being. Medical students are expected to learn and master a huge amount of knowledge, attitudes and skills for which they have to work hard which in turn put them under a lot of stress. The present study was conducted with the objectives to assess and quantify the perceived stress, stressors and their severity and to assess the stressors associated with stress. Methods: The present cross sectional study was under taken at Rohilkhand Medical College and Hospital, Bareilly, India. The study was conducted during October - November 2014. All students pursuing under-graduation in Allopathy Medicine (MBBS) were invited to participate in this study. Perceived stress was measured using the perceived stress scale (PSS-10). The students were asked to indicate if any of the 29 stressors had been affecting them. Binary logistic regression analysis was carried out to access the stressors significantly influencing the stress. Results: 48.0% of the students were found to be stressed. Most frequently occurring academic sources of stress, psychosocial, and health related stressors reported by students as often/always were performance in examination (40.3%), lack of entertainment in the institution (48.5%) and quality of food in mess (50.7%). Feeling of adoption of wrong carrier field, frequency of examination and lack of time for recreation, lack of entertainment in the institution and sleep disorder were found to be significantly associated with stress. Conclusions: Medical education renders significant amount of stress to the students. There is need for measures to reduce such stress and future research.